An Integrated Proteomics and Metabolomics Strategy for the Mechanism of Calcium Oxalate Crystal-Induced Kidney Injury - Gao, Songyan; Chao, Yufan; Li, Na; Li, Henghui; Zhao, Hongxia; Liu, Xinru; Chen, Wei; Dong, Xin (Frontiers in Medicine, 2022)
Renal fibrosis is the pathological repair reaction of the kidney to chronic injury, which is an important process of chronic kidney disease (CKD) progressing to end-stage renal failure. Nephrolithiasis is one of the most common renal diseases, with waist and abdomen pain, hematuria, urinary tract infection, and other clinical symptoms, which can increase the risk of renal fibrosis. Oxalate crystal-induced kidney injury is an early stage of nephrolithiasis; it is of great significance to explore the mechanism for the prevention and treatment of nephrolithiasis. A rodent model of calcium oxalate (CaOx) crystal-induced kidney injury was used in the present study, and a network analysis method combining proteomics and metabolomics was conducted to reveal the mechanism of crystal kidney injury and to provide potential targets for the intervention of nephrolithiasis. Using the metabolomics method based on the UHPLC-Q/TOF-MS platform and the iTRAQ quantitative proteomics method, we screened a total of 244 metabolites and 886 proteins from the kidney tissues that had significant changes in the Crystal group compared with that in the Control group. Then, the ingenuity pathway analysis (IPA) was applied to construct a protein-to-metabolic regulatory network by correlating and integrating differential metabolites and proteins. The results showed that CaOx crystals could induce inflammatory reactions and oxidative stress through Akt, ERK1/2, and P38 MAPK pathways and affect amino acid metabolism and fatty acid β-oxidation to result in kidney injury, thus providing an important direction for the early prevention and treatment of nephrolithiasis.